2022
DOI: 10.1007/s00330-021-08483-8
|View full text |Cite
|
Sign up to set email alerts
|

CT measures of femoral and tibial version and rotational position of femoral and tibial components of knee replacements: limitations in reliability and suitability for routine clinical practice

Abstract: Objectives Rotational malalignment of knee replacements as measured on CT is understood to be associated with poor outcomes. The aim of this study is to measure the inter-rater and intra-rater reliability of measures of femoral and tibial version in the native arthritic knee and postoperative TKR component position using CT. Methods Eighty patients underwent CT of the knee before and after total knee replacement. Preoperative femoral and tibial version and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Currently, three-dimensional CT has become increasingly popular as it can mitigate several factors, including lower limb position and joint contracture, which may influence the accuracy and reliability of conventional two-dimensional CT imaging. 27 28) Lastly, our study included predominantly female patients (n = 86), which may be associated with different femoral geometry compared to male patients. Koh et al 29) demonstrated gender differences in both medial and lateral posterior condyle morphology, and this could contribute to variation in the PCA between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, three-dimensional CT has become increasingly popular as it can mitigate several factors, including lower limb position and joint contracture, which may influence the accuracy and reliability of conventional two-dimensional CT imaging. 27 28) Lastly, our study included predominantly female patients (n = 86), which may be associated with different femoral geometry compared to male patients. Koh et al 29) demonstrated gender differences in both medial and lateral posterior condyle morphology, and this could contribute to variation in the PCA between men and women.…”
Section: Discussionmentioning
confidence: 99%
“…In the AURORA protocol [ 25 ] the tibial antero-posterior axis was defined by the tibial tubercle and the PCL insertion. Yoshino et al [ 24 ] defined the coronal plane as a vertical to the “Akagi line.” However, other studies have demonstrated that these landmarks are hard to define and have low interobserver reliability [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yoshino et al [24] defined the coronal plane as a vertical to the "Akagi line." However, other studies have demonstrated that these landmarks are hard to define and have low interobserver reliability [26,27].…”
Section: Postoperative Deformitymentioning
confidence: 99%
“…FCR was determined as the angle between the trans‐epicondylar axis and posterior condylar axis. TCR was measured according to the Berger protocol [37]. To determine the position error, internal rotation of the femoral and tibial component was negative, and external rotation was positive.…”
Section: Methodsmentioning
confidence: 99%